Correlation Between Fe/S/As Speciation Transformation and Depth Distribution of Acidithiobacillus ferrooxidans and Acidiphilium acidophilum in Simulated Acidic Water Column - Zhou, Yu-hang; Wang, Can; Liu, Hong-chang; Xue, Zhen; Nie, Zhen-yuan; Liu, Yue; Wan, Jiao-li; Yang, Yu; Shu, Wen-sheng; Xia, Jin-lan (Frontiers in Microbiology, 2022)
It is well known that speciation transformations of As(III) vs. As(V) in acid mine drainage (AMD) are mainly driven by microbially-mediated redox reactions of Fe and S. However, these processes are rarely investigated. In this study, columns containing mine water were inoculated with two typical acidophilic Fe/S-oxidizing/reducing bacteria (the chemoautotrophic Acidithiobacillus (At.) ferrooxidans and the heterotrophic Acidiphilium (Aph.) acidophilum), and three typical energy substrates (Fe2+, S0, and glucose) and two concentrations of As(III) (2.0 and 4.5 mM) were added. The correlation between Fe/S/As speciation transformation and bacterial depth distribution at three different depths, i.e., 15, 55, and 105 cm from the top of the columns, was comparatively investigated. The results show that the cell growth at the top and in the middle of the columns was much more significantly inhibited by the additions of As(III) than at the bottom, where the cell growth was even promoted on days 24-44. At. ferrooxidans dominated over Aph. acidophilum in most samples collected from the three depths, but the elevated proportions of Aph. acidophilum were observed in the top and bottom column samples when 4.5 mM As(III) was added. Fe2+ bio-oxidation and the Fe3+ reduction coupled to As(III) oxidation occurred for all three depths of the columns. At the column top surfaces, jarosites were formed, and the additions of As(III) could lead to the formation of the amorphous FeAsO4·2H2O. Furthermore, the higher As(III) concentration could inhibit Fe2+ bio-oxidation and the formation of FeAsO4·2H2O and jarosites. S oxidation coupled to Fe3+ reduction occurred at the bottom of the columns, with the formations of FeAsO4·2H2O precipitate and S intermediates. The formations of FeAsO4·2H2O and jarosites at the top and bottom of the columns could adsorb to and coprecipitate with As(III) and As(V), resulting in the transfer of As from solution to solid phases, thus further affecting As speciation transformation. The distribution difference of Fe/S energy substrates could apparently affect Fe/S/As speciation transformation and bacterial depth distribution between the top and bottom of the water columns. These findings are valuable for elucidating As fate and toxicity mediated by microbially driven Fe/S redox in AMD environments.